2014
DOI: 10.1097/jsc.0000000000000237
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fatigue From Resistance Training on Barbell Back Squat Biomechanics

Abstract: Exhaustive resistance training programs that have been previously referred to as extreme conditioning protocols have increased in popularity in military and civilian populations in recent years. However, because of their highly fatiguing nature, proprioception is likely altered during such programs that would significantly affect the safety and efficacy of such programs. Therefore, the purpose of this study was to assess the alterations in movement patterns that result from extreme conditioning protocols and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
42
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 13 publications
2
42
0
2
Order By: Relevance
“…The authors reported changes in squat technique and suggested there was evidence of increased likelihood of injury as fatigue developed. In particular, the authors measured reduced movement at the knee joint (abbreviated squat depth) and determined that injury risk was increased due to greater forward lean of the trunk [2]. However, counter-intuitively, the results showed that squat depth increased and the amount of forward lean decreased across the repetitions as fatigue developed.…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…The authors reported changes in squat technique and suggested there was evidence of increased likelihood of injury as fatigue developed. In particular, the authors measured reduced movement at the knee joint (abbreviated squat depth) and determined that injury risk was increased due to greater forward lean of the trunk [2]. However, counter-intuitively, the results showed that squat depth increased and the amount of forward lean decreased across the repetitions as fatigue developed.…”
Section: Introductionmentioning
confidence: 95%
“…However, counter-intuitively, the results showed that squat depth increased and the amount of forward lean decreased across the repetitions as fatigue developed. The authors interpreted these results as evidence of participants adopting a self-preservation behavior at the beginning of the highly fatiguing task and that when they were confident in their ability to complete the protocol the participants adopted more appropriate and effective movement patterns [2].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations